Climate change: A threat towards achieving ‘Sustainable Development Goal number two’ (end hunger, achieve food security and improved nutrition and promote sustainable agriculture) in South Africa - Mugambiwa, Shingirai S. (Jamba, 2017)
This article aims to assess the impacts of climate change towards the achievement of Sustainable Development Goal number two (SDG 2) as well as examining the poverty alleviation strategies by subsistence farmers in South Africa. Widespread hunger and poverty continue to be among the most life-threatening problems confronting mankind. Available statistics show that global poverty remains a serious challenge around the world. Across the globe, one in five people lives on less than $1 a day and one in seven suffers from chronic hunger. Similarly, the developing world is adversely affected by poverty and hunger. In the sub-Saharan Africa, research has revealed a higher prevalence of hunger, malnutrition, poverty and food insecurity. SDG 2 focuses more on eliminating hunger and promoting sustainable agriculture. The study employed an exploratory design and a qualitative method. Snowball sampling was used in selecting relevant sources which led the researchers to other research work on the same field through keywords and reference lists. The researchers employed discourse analysis to analyse data. The study discovered that there are numerous potential effects climate change could have on agriculture. It affects crop growth and quality and livestock health. Farming practices could also be affected as well as animals that could be raised in particular climatic areas. The impact of climate change as well as the susceptibility of poor communities is very immense. The article concludes that climate change reduces access to drinking water, negatively affects the health of people and poses a serious threat to food security.